- four *(sin(two *x)^ two /cos(two *x)^ two - one)/log(two) = zero
minus 4 multiply by ( sinus of (2 multiply by x) squared divide by co sinus of e of (2 multiply by x) squared minus 1) divide by logarithm of (2) equally 0
minus four multiply by ( sinus of (two multiply by x) to the power of two divide by co sinus of e of (two multiply by x) to the power of two minus one) divide by logarithm of (two) equally zero
-4*(sin(2*x)2/cos(2*x)2 - 1)/log(2) = 0
-4*sin2*x2/cos2*x2 - 1/log2 = 0
-4*(sin(2*x)²/cos(2*x)² - 1)/log(2) = 0
-4*(sin(2*x) to the power of 2/cos(2*x) to the power of 2 - 1)/log(2) = 0
-4(sin(2x)^2/cos(2x)^2 - 1)/log(2) = 0
-4(sin(2x)2/cos(2x)2 - 1)/log(2) = 0
-4sin2x2/cos2x2 - 1/log2 = 0
-4sin2x^2/cos2x^2 - 1/log2 = 0
-4*(sin(2*x)^2 divide by cos(2*x)^2 - 1) divide by log(2) = 0